Why do leaves change color? - Maestro, Betsy; Krupinski, Loretta (New York : HarperCollins, 1994)
Explains how leaves change their colors in autumn and then fall from the tree as it prepares for winter.
Elem. School Library Collection
School Library Journal
Wilson's Children
3.3
K-3
K-3
Keywords: Fall foliage -- Juvenile literature; Leaves -- Color -- Juvenile literature; Trees -- Juvenile literature; Fall foliage; Leaves -- Color; Trees; Autumn; Leaves; Leaves -- Color; Trees